Propriedades elétricas de nanoantena de grafeno - TAVARES, Simone Cristina da Costa (Universidade Federal do Pará, 2017)
The incessant rush for discovering new materials and the search for new solutions to the tech-nological problems and equipment that have devices with better performance than the currently available, operating at ever smaller scales led us to study antennas that allow to occupy an increasingly small space. This permitted us to show the study of the electronic carbon nanotube structure and the electrical properties of graphenenano-antenna as its precursors. The develop-ment of antennas made of carbon nanotube and graphene is, in the moment, a technological possibility opened to state of art. In this paper we investigate the electronic transport for gra-phene organic material using it as a nano-antenna where we present simulations of quantum calculations derived from Hartree-Fock theory and semi-empirical method, which is given by the electron charge distribution along the structure. The structural parameters of the optimized structure have been fully calculated, including external electric field across the matrix layer of closed Roothaan-Hall model. Featuring a characteristic related to the electrical response which results a transistor device field effect, with capacitance and operating frequency in 90 THz un-der an operating voltage around the 0,82 V rectification and we show, also, the Fowler-Nord-heim model and Millikan -Lauritsen for graphene structure.